Recopilación de memoria colectiva con base narrativa oral costumbrista para propuesta artística con estilo Lowbrow - Montaño Escobar, Javier Alexander (2023)
The research project entitled: COLLECTIVE MEMORY COLLECTION BASED ON ORAL COSTUMBRISTA NARRATIVE FOR ARTISTIC PROPOSAL WITH LOWBROW STYLE, pursues the purpose of remembering part of the intangible heritage of the Lojano tradition, based on recapitulating that oral narrative that has remained present from generation to generation and express it through the graphic language of the artistic current called Lowbrow, through a last plastic proposal consisting of five final pictorial works. For this research work, the objective was to make a pictorial proposal based on the study of the artistic and aesthetic foundations of the Lowbrow movement, using the analysis of different undocumented local narratives as a motif. For this purpose, a qualitative approach was used, based on the application of the deductive-inductive method, allowing to channel of the different aspects of the Lowbrow current and converge them in the realization of the pictorial sample, in addition to the collection of data and contexts derived from the direct observation of local narratives. Moreover, the empirical method was used to research the different sensations and emotions immersed in the people interviewed in each story, and through the experimental method, field studies and personal reinterpretations of each story were obtained as a result to materialize in the pre-production, production and post-production processes. Finally, a satisfactory result was obtained, based on theory and practice evidenced in five pictorial works that contain specific fragments of the chosen narratives. Keywords: Lowbrow Art; Painting; Customs; Oral Tradition; Collective Memory.